Covid 19 : Analisis Perbedaan Harga Saham Pada Perusahan Telekomunikasi - Ronald N Girsang (Jurnal Ilmiah Dan Karya Mahasiswa, 2023)
This research is to test whether there is a difference in share prices in telecommunications companies before and during the Covid-19 pandemic. The research method used in this research is a quantitative research method in the form of a comparative descriptive study to compare share prices of telecommunications companies before and during the Covid 19 pandemic (2017-2021). The population in this research is all telecommunications companies listed on the Indonesia Stock Exchange with a total of 19 companies, with the observation period before Covid being 2019 and during the pandemic in 2020 with. The results of this study show that there is no significant difference in stock prices before and during the Covid-19 pandemic, this is indicated by a significance value of 0.535 which is greater than 0.05.